Diseño y construcción de una máquina semiautomática portátil para recargar extintores de PQS (polvo químico seco) desde 1 kg hasta 45 kg - Ayala Toapanta, Víctor Eduardo (2018)
This research has as objective to design and build a semiautomatic portable machine to recharge dry chemical powder fire extinguishers, which are used in the industrial safety field. The reason for building such a machine emerges from the need of the companies in charge of these kinds of fire extinguishers. Regarding the design and construction of a device with these characteristics, it can be said that it will help in the industrial safety field, since it will aid with the corrective maintenance of the A, B, C type instruments used for killing fires. Also, the use of a semiautomatic machine like this will reduce contamination produced when recharging dry chemical powder fire extinguishers in the workplace. Concerning the productivity, a semiautomatic device like this diminishes the time used for each recharge thanks to its easy handling and the possibility of being used by just one person. In order to fulfill the objective, an analysis of the availability of materials was carried out in the Ecuadorian market, so that the portable machine to recharge dry chemical powder extinguishers could be designed and constructed from available materials in the market as well as with simple parts made in machining centers. Furthermore, a research of costs was carried out, so the investment budget generates a retail price that helps make this portable machine affordable in the market as well as in its manufacturing.